Performance Characteristics of Head-Worn Antenna based on Dielectric Substrate Over WBAN Application - Mumin, Abdul Rashid .O.; Alias, R.; Abdullah, Jiwa; Abdulhasan, Raed A; Dahlan, Samsul Haimi; joret, Ariffuddin (International Journal of Engineering and Technology, 2018)
Performance characteristics of head-worn antenna based on dielectric substrate for WBAN application with various dielectric constant for square slot patch antenna are demonstrated in this paper. The impact of Electromagnetic (EM) energy from antenna towards human head and on antenna performance changes due to human head proximity are explored in this paper. The human head exposed to 5.8 GHz on ISM frequency band and radiation pattern, return loss, efficiency, and bandwidth and SAR distribution value performance have been thoroughly explored. However, decreasing the antenna size is a great topic â€Žof antenna development, which differentiates antenna performance for a small antenna. Multilayered human head phantom having five layers are constructed based on different tissues and these tissues represent human head parts such as (Skin, fat, Cerebrospinal fluid (CSF), bone and brain), all of each tissues are based on their electromagnetic properties and set at 5.8GHz.The proposed antenna with human head model simulated through (FDTD) using CST and variation of parameters of antenna with MATLAB.Â Antenna with FR4 substrate produces the highest SAR values while antenna with RT5880 substrate has the lowest SAR value 0.206 W/kg and 0.0784 W/kg at 5.8 GHz frequency exposed for 10g tissue respectively. It can be observed that the radiation pattern shows that the antenna gain with substrate of Rogers RT5880 is increased from front â€“to-back from 7.1 to 7.29 dB in the free space and on human head respectively. A good agreement between simulation and measurements in free space are obtained. The presented prototype has a potential to work for ISM applications.